1998
DOI: 10.1046/j.1365-2168.1998.00778.x
|View full text |Cite
|
Sign up to set email alerts
|

Active or passive chest drainage after oesophagectomy in 101 patients: a prospective randomized study

Abstract: Passive drainage did not reduce hospital stay, but was as safe and effective as the active system in draining the pleural cavity after uncomplicated oesophagectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…In patients who underwent esophagectomy, active (15 cm water) suction and passive drainage were compared in one report. 9 There was no difference in the prevalence of pneumothorax, nor was there any difference in the size and duration of the pneumothorax. It was concluded that passive drainage was as safe and effective as the active system in draining the pleural cavity after esophagectomy.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In patients who underwent esophagectomy, active (15 cm water) suction and passive drainage were compared in one report. 9 There was no difference in the prevalence of pneumothorax, nor was there any difference in the size and duration of the pneumothorax. It was concluded that passive drainage was as safe and effective as the active system in draining the pleural cavity after esophagectomy.…”
Section: Discussionmentioning
confidence: 82%
“…Whether active suction to chest drains is needed after thoracic procedures has not been adequately studied. In patients who underwent esophagectomy, active (15 cm water) suction and passive drainage were compared in one report 9 . There was no difference in the prevalence of pneumothorax, nor was there any difference in the size and duration of the pneumothorax.…”
Section: Discussionmentioning
confidence: 99%
“…However, esophagectomy usually involves an extensive thoracic procedure, and temporary chest drainage still is considered necessary to prevent pulmonary compression by accumulation of air or fluid . Although direct evidence is lacking for esophagectomy, literature on open pulmonary surgery suggests that the use of a single drain is safe and that drains can be removed when producing less than 200 mL per day . However, owing to the sparsity of literature specifically addressing chest drainage after esophagectomy, postoperative drainage protocols vary widely, and more research is needed to achieve consensus.…”
Section: Enhanced Recovery After Esophagectomy In the Postoperative Smentioning
confidence: 99%
“…107 A cardiac RCT found removing drains at 24 hours rather than 48 hours to be equivalent, with trends toward improved pain and ventilation. 115 Transabdominal chest drainage has been described in 2 cohort studies, although both had relatively high rates of reaccumulation requiring intervention. 111 Method of Drainage.…”
Section: Chest Drainsmentioning
confidence: 99%